Afiche de invitacion a Mitin. - Centro de Estudios Teológicos de la Amazonía (CETA) (My University, 1900)
SPANISH: Se observo la fachada de una vivienda rural amazonico con afiches publicitarios y uno de invitacion a reunion, en zona del Paucarquillo/Distrito de Pebas - Rion Amazonas.
ENGLISH: the façade of an Amazonian rural house was observed with advertising posters and one of invitation to meeting, in the area of Paucarquillo / District of Pebas - Rion Amazonas

SPANISH: Se observo la fachada de una vivienda rural amazonico con afiches publicitarios y uno de invitacion a reunion, en zona del Paucarquillo/Distrito de Pebas - Rion Amazonas.
ENGLISH: the façade of an Amazonian rural house was observed with advertising posters and one of invitation to meeting, in the area of Paucarquillo / District of Pebas - Rion Amazonas
Poster of invitation to Rally
Keywords: Iquitos (Perú)|~|Rural houses|~|Perú|~|Amazonian cottages|~|Perú|~|Rural houses|~|Iquitos (Perú)|~|Casas Rurales|~|Perú|~|Casas rurales amazonicos|~|Perú|~|Casas Rurales|~|Iquitos (Perú)|~|Rural Houses|~|Peru|~|Amazonian cottages|~|Peru|~|Rural Houses